2011
DOI: 10.1007/s00423-011-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Flow distribution during infusion of UW and HTK solution in anaesthetised rats

Abstract: Infusion of HTK and UW solution into anaesthetised rats results in a flow distribution which is similar to that in normal animals in most abdominal organs, but there is a reduction in islet blood perfusion by UW but not HTK solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In situ perfusion can therefore quite conceivably not provide the requirements to build up an adequate perfusion flow since in this case the driving pressure is considerably low [12]. In contrast to this, ex situ perfusion is independent of any aortic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ perfusion can therefore quite conceivably not provide the requirements to build up an adequate perfusion flow since in this case the driving pressure is considerably low [12]. In contrast to this, ex situ perfusion is independent of any aortic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a constant volume of 100 ml normal saline suspension (NaCl 0.9%) containing equal amounts of MPs for both treatment groups revealed that 100% of MPs were trapped inside the kidney receiving ex situ perfusion whereas only small amounts (8%) reached the target tissue by in situ perfusion. This indicates a loss of perfusion solution into other regions of the body when applying in situ perfusion [12]. …”
Section: Discussionmentioning
confidence: 99%